Emotional Expression of Public Communication Post COVID-19 Era In Educational Context - Angela Audrey Sutanto; Inri Inggrit Indrayani; Astri Yogatama (Universitas Prof. Dr. Moestopo (Beragama), 2024)
This research aims to examine the emotional expression of nonverbal communication performed by scholars during presentations as a post-pandemic public communication practice. In the age of globalization, one of the necessary talents is public communication. A presentation that tries to transmit knowledge about a topic to the audience effectively is a familiar public communication technique scholars perform. Building a connection with the audience is one way to create effective communication, one of which is emotional expression in the form of nonverbal communication through gestures and microexpressions. Public communication skills have deteriorated, particularly during the COVID-19 epidemic, as have emotional expressions in nonverbal communication. With previous theoretical perspectives in gesture and microexpression, this study employed a quantitative-descriptive content analysis technique with categorical analysis units. Researchers examined 49 video recordings of scholars’ presentations from February to March 2023. The study's findings revealed that when scholars practiced public communication in class, they employed scared emotions for gestures and calm emotions for microexpressions. This study suggests the significance of public communication training or coaching, particularly for nonverbal emotional displays in presentations, to fulfill communication goals.